2004
DOI: 10.1021/jm049884d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Conformational Analysis of a Non-Amidine Factor Xa Inhibitor That Incorporates 5-Methyl-4,5,6,7-tetrahydrothiazolo[5,4-c]pyridine as S4 Binding Element

Abstract: Our exploratory study was based on the concept that a non-amidine factor Xa (fXa) inhibitor is suitable for an orally available anticoagulant. We synthesized and evaluated a series of N-(6-chloronaphthalen-2-yl)sulfonylpiperazine derivatives incorporating various fused-bicyclic rings containing an aliphatic amine expected to be S4 binding element. Among this series, 5-methyl-4,5,6,7-tetrahydrothiazolo[5,4-c]pyridine type 61 displayed orally potent anti-fXa activity and evident prolongation of prothrombin time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(23 citation statements)
references
References 47 publications
1
19
0
2
Order By: Relevance
“…191 The cocrystal structure of 160 bound to fXa (PDB code 1V3X) confirmed that the chloronaphthalenyl moiety occupies the S1 pocket and that the methyltetrahydrothiazolopyridine moiety binds to the S4 subsite, as expected. 191 Using structure-based design based on 129 and the cocrystal structure of 302 (FXV673) with fXa, the P4 in the piperazine series was replaced with a pyridine N-oxide moiety and yielded 161 (fXa IC 50 5 8.6 nM, EC 2 Â PT 5 4.0 mM) with improved potency. 192,193 Installation of a pyridine N-oxide at P4 as found in 163 (fXa IC 50 (Fig.…”
Section: Group 4 Piperazine and Ketopiperazine Scaffoldssupporting
confidence: 64%
“…191 The cocrystal structure of 160 bound to fXa (PDB code 1V3X) confirmed that the chloronaphthalenyl moiety occupies the S1 pocket and that the methyltetrahydrothiazolopyridine moiety binds to the S4 subsite, as expected. 191 Using structure-based design based on 129 and the cocrystal structure of 302 (FXV673) with fXa, the P4 in the piperazine series was replaced with a pyridine N-oxide moiety and yielded 161 (fXa IC 50 5 8.6 nM, EC 2 Â PT 5 4.0 mM) with improved potency. 192,193 Installation of a pyridine N-oxide at P4 as found in 163 (fXa IC 50 (Fig.…”
Section: Group 4 Piperazine and Ketopiperazine Scaffoldssupporting
confidence: 64%
“…The final map clearly showed electron density for all main chain atoms from residues 23 to 114, the inhibitor 2, 96 water molecules, two sulfate ions, and one 3-morpholinopropanesulfonic acid molecule. Alternative conformations have been included for residues 29,35,39,46,57,63,76,81, and 86. Surface complementarity was investigated with the SC program from the CCP4 program suite with use of the default parameters.…”
Section: Methodsmentioning
confidence: 99%
“…[38] Für eine Weiterentwicklung von Daiichi, die Verbindung 25, konnte dieser Bindungsmodus mit Chlornaphthalin in der S1-Seite explizit gezeigt werden. [39] Eine weitere Chlornaphthylverbindung, TAK-442 (26), befindet sich in Phase II der klinischen Entwicklung für die Behandlung von Lungenembolien, Schlaganfall und akutem Koronarsyndrom. [40] Auch hier bestätigt die kristallographisch bestimmte Struktur im Komplex mit humanem FXa, dass die 6-Chlornaphthylgruppe die S1-Substratbindungstasche besetzt, wobei das Chloratom eine hydrophobe Wechselwirkung mit dem Aren von Tyr228 eingeht.…”
Section: Faktor-xa-inhibitorenunclassified